2008
DOI: 10.1162/jocn.2008.20142
|View full text |Cite
|
Sign up to set email alerts
|

Feedforward and Recurrent Processing in Scene Segmentation: Electroencephalography and Functional Magnetic Resonance Imaging

Abstract: In texture segregation, an example of scene segmentation, we can discern two different processes: texture boundary detection and subsequent surface segregation [Lamme, V. A. F., Rodriguez-Rodriguez, V., & Spekreijse, H. Separate processing dynamics for texture elements, boundaries and surfaces in primary visual cortex of the macaque monkey. Cerebral Cortex, 9, 406–413, 1999]. Neural correlates of texture boundary detection have been found in monkey V1 [Sillito, A. M., Grieve, K. L., Jones, H. E., Cudeiro, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
143
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(160 citation statements)
references
References 45 publications
17
143
0
Order By: Relevance
“…The size of the individual squares of the checkerboard was 2.5°by 2.5°visual arc. Although this results in relatively long presentation times for the texture stimuli compared to earlier work, we cannot expect that the longer presentation times will have a large effect on the processing of textures (compare e.g., Fahrenfort, Scholte, & Lamme, 2007, who have used very brief presentation times, and Scholte et al, 2008, using long presentation times, yielding very similar results).…”
Section: Visual Stimulationmentioning
confidence: 68%
See 2 more Smart Citations
“…The size of the individual squares of the checkerboard was 2.5°by 2.5°visual arc. Although this results in relatively long presentation times for the texture stimuli compared to earlier work, we cannot expect that the longer presentation times will have a large effect on the processing of textures (compare e.g., Fahrenfort, Scholte, & Lamme, 2007, who have used very brief presentation times, and Scholte et al, 2008, using long presentation times, yielding very similar results).…”
Section: Visual Stimulationmentioning
confidence: 68%
“…All statistics are based on the activity in channel Oz according to the International 10-20 System. This electrode was selected on the basis of previous studies (e.g., Scholte et al, 2008;Caputo & Casco, 1999;Lamme, Van Dijk, & Spekreijse, 1992).…”
Section: Eeg Recording and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work using transient VEPs to study the segmentation of textures into regions has indicated that a differentiation between uniform and segmented stimuli occurs as early as 90-115 ms (Bach and Meigen, 1992;Caputo et al, 1999;Lamme et al, 1992;Scholte et al, 2006Scholte et al, , 2008. Texture-segmentation-related activity localizes to V1 (Appelbaum et al, 2012;Lamme et al, 1992Lamme et al, , 1998.…”
Section: From Representation To Decisionmentioning
confidence: 99%
“…Feedback accomplishes this by a differential effect on neural activity; it enhances figure responses and lowers background responses (Supèr & Romeo, 2011). Such push-pull effect is also observed in neurons of the visual cortex responding to figure-ground textures (Supèr et al, 2001a;Landman et al, 2003a;Scholte et al, 2008). Moreover, the model shows that feedback especially enhances figure-ground signal when the feedforward input is relatively weak.…”
Section: Feedforward Segregation Of Figure-groundmentioning
confidence: 69%